The feeding ecology of curlew sandpipers "Calidris Ferruginea" in the South-Western Cape, South Africa - Puttick, Gillian Margaret (Department of Biological Sciences, 2024)
Spatial and temporal changes in the distribution of food organisms potentially available to curlew sandpipers Calidris ferruginea at Langebaan Lagoon (33°s, 18°E), South Africa, are described for the period February 1974 - March 1975. Seasonal changes in the diet of curlew sandpipers foraging in the intertidal sandflats and marshes were studied, and the food taken by male and female, and immature and adult, birds was compared. The daily and seasonal activity of curlew sandpipers was monitored during March 1974 - March 1975 and this also provided information on the birds' foraging behaviour and foraging techniques, their use of microhabitat and their foraging related to shore level. Variations during the austral summer in the density and the foraging of curlew sandpipers related to the density of their prey was investigated in the light of Royama's (1971) theory of profitability. The foraging behaviour and spatial distribution of foraging male and female curlew sandpipers at Kommetjie (34 o8°s, 18 19°E) was compared, since curlew sandpipers show sexual dimorphism with females having-longer culmens. The energy requirements and energy intake of curlew sandpipers at Langebaan Lagoon are described. The gross annual production of the benthic invertebrates potentially available to the birds was estimated, as well as the birds' impact on this. The study of trophic relationships within the world's major ecosystems has provided a significant thrust to ecological investigations over the past fifteen years. Ecologically 'sensitive' areas such as wetlands and intertidal zones, which form the interface between different ecosystems, have been receiving attention more recently. However, apart from terrestrial ecosystems, very little information is available on trophic relationships within other southern African ecosystems and within wetlands in particular. Furthermore, although Siegfried (in prep.) has described the seasonal abundance of migratory birds at southern African wetlands as 'a major ecological phenomenon', there is at present no clear understanding of resource partitioning among Palaearctic waders on the one hand and resident species on the other in southern Africa. This dissertation attempts to contribute information useful in understanding the trophic relationships within a marine lagoon ecosystem in the south-western Cape, South Africa, and to elucidate the resource utilization of the most abundant Palaearctic migrant there, the curlew sandpiper Calidris ferruginea. The curlew sandpiper is a common member of .the avifauna of estuaries and lagoons around the coast of South Africa (McLachlan & Liversidge 1970). In particular, the population of curlew sandpipers varies between 37 000 and 55 000 birds at Langebaan Lagoon (33°s, 18°E) during the austral summer (Pringle & Cooper 1975, Summers 1977), and is as high as 12 000 in the austral winter (Pringle & Cooper 1975). Curlew sandpipers comprise 64% of the wader population which migrates seasonally to Langebaan Lagoon (Pringle & Cooper 1975).